Distinctive clinicopathological features and KRAS and IDH1/2 mutation status of cholangiolocellular carcinoma. Issue 1 (8th December 2019) - Kusano, Hironori; Naito, Yoshiki; Mihara, Yutaro; Kondo, Reiichiro; Ogasawara, Sachiko; Akiba, Jun; Nakashima, Osamu; Yano, Hirohisa
Abstract : Aim: Cholangiolocellular carcinoma (CLC) is classified as a subtype of combined hepatocellular cholangiocarcinoma with stem‐cell features (CHC‐SC) in the latest World Health Organization classification. This subclassification of CHC‐SCs is controversial and the relevance of such classification is unclear. Methods: We analyzed a series of CHC‐SCs and intrahepatic cholangiocarcinoma (iCCA) to clarify the clinicopathological features and mutational status of each tumor. Results: Background liver disease, fibrosis stage, microvascular invasion, nodal metastasis, and IDH1/2 mutation status were associated with their histology. Compared with the intermediate cell subtype of CHC‐SC (CHCs‐SC‐int), CLCs were less frequently associated with chronic viral hepatitis, and showed lower levels of serum alpha‐fetoprotein. Compared with iCCAs, CLCs showed lower levels of serum carbohydrate antigen 19‐9 (CA19‐9) and a lower frequency of expression of S100P. Patients with iCCA showed worse overall survival than those with CLC or CHC‐SC‐int. In patients with iCCA, CLC, or CHC‐SC‐int, a histology of iCCA, microvascular invasion, and serum CA19‐9 value of >100 U/mL were significant poor prognostic factors for overall survival in univariate analysis. Multivariate analysis showed that a high serum CA19‐9 value was an independent poor prognostic factor for overall survival. Conclusions: Patients with CLC are likely to have a different etiology and mutational background from those with CHC‐SC‐int. Their clinicopathological manifestations are also different from those with classic iCCA. Our results suggest that CLC might be a distinct entity among primary liver carcinomas.